Epidemiology and risk factors associated with surgical site infection following surgery on thoracic aorta. Issue 14 (11th July 2018) - Morikane, K.
Abstract: Surgical site infection (SSI) following cardiovascular surgery has been well documented, possibly owing to its highly invasive nature, but SSI following surgery on the thoracic aorta has not. This study aimed to describe the epidemiology and assess risk factors associated with the latter in Japan using a national database for SSI. Data on surgery on thoracic aorta performed between 2012 and 2014 were extracted from the Japan Nosocomial Infections Surveillance (JANIS) database. Risk factors were assessed initially by univariate analysis, and then entered into a logistic regression model for final evaluation. The cumulative incidence of SSI was 4.1% (146/3538) and staphylococci were the most frequent pathogens isolated. Factors such as the duration of operation, emergency surgery and male gender were significantly associated with SSI. These findings differ from previous studies on open heart and coronary artery bypass surgery, in which the American Society of Anesthesiologists (ASA) score was significantly associated with SSI, but gender was not. This study suggests that risk stratification in the JANIS system might be improved by incorporating additionally identified factors for risk adjustment, when comparing the incidence of SSI between hospitals.